A brief analysis of the role of taijiquan animation works in the promotion of Taijiquan among young people - Li, Qi; Chu, Jijun (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: As a world intangible cultural heritage, Tai Chi is a traditional ethnic sports event in China, with a long history and profound cultural accumulation. It has the unique value and effect of comprehensive exercise, both inside and outside, strong interest, edifying temperament, everyone can practice, physical fitness and so on. And it plays an irreplaceable important role in the new era of national fitness wave. "Healthy China 2030" plan is put forward, to develop the popular forms of sports, encourage the development of suitable for different people, different region characteristic features of the sports, supporting the promotion of taijiquan, qigong, such as national traditional sports, and formulate implementation of youth, women, the elderly, occupational groups and special groups such as physical health intervention program for the disabled. However, the popularity of taijiquan is uneven: from the perspective of age composition, the participation of teenagers is still very low; From the perspective of interests and hobbies, teenagers pay much less attention to Tai Chi than the middle-aged and old; From the perspective of value effect, people pay more attention to the health effect of Tai Chi and ignore the actual combat effect and cultural inheritance of Tai Chi as a traditional martial arts. This is not consistent with the characteristics of taijiquan, which is "everyone can practice" and "comprehensive exercise". It also restricts and affects the inheritance of Chinese traditional sports culture. At present, the research on Taijiquan is mostly from the perspective of development status, development strategy and movement mechanism, while the research on the causes of unequal development of Taijiquan is relatively lacking. Methods: Using the methods of literature, mathematical statistics, questionnaire and expert interview, this paper takes the influence of Taijiquan animation works on the promotion of Taijiquan in the group of teenagers aged 10 to 24 as the research object. From the perspective of taijiquan animation works favored by teenagers, the characteristics of Taijiquan and teenagers' value orientation are combined. This paper analyzes and expounds the role and effect of Taijiquan animation works on the promotion of Taijiquan among young people, aiming at exploring the feasibility and implementation path of guiding young people to enrich their cognition of Taijiquan through Taijiquan animation works as a breakthrough, and then training them to advocate and practice Taijiquan. Results: (1) teenagers learn tai chi chuan channel is few, most of the elements by watching tai chi chuan, film and television works and relevant taijiquan martial arts novels, etc. To learn tai chi chuan, only a handful of teenagers by taijiquan event or practicing taijiquan around the relatives and friends to learn tai chi chuan, cause teenagers stay the cognition of taijiquan in the aspect of art; (2) Sports animation is very popular among teenagers, and Taijiquan animation works will be an effective way and measure to promote taijiquan to spread and learn among teenagers. However, due to the low quality and small number of existing taijiquan animation works, it blocks the effective channel for teenagers to understand, accept, like and participate in Taijiquan. (3) There is a great difference between the popular taijiquan film and television works and the animation forms that teenagers love and are willing to accept, which leads to the deviation of teenagers' understanding of Taijiquan; (4) With the growth of age, teenagers' interest in Tai Chi is on the rise; (5) Most teenagers think that Taijiquan is a national fitness sport that can strengthen the body and cultivate the sentiment. Based on the skillful use, it can be used for self-defense and has a certain attack power, indicating that taijiquan has a certain ideological basis for its promotion among teenagers. (6) Most teenagers think that the current popular taijiquan films and television works are real, and at the same time, they overstate the actual combat effect of Taijiquan; (7) Animation works have a strong value guiding role for teenagers. Taijiquan animation works can play a unique and effective role in guiding teenagers to actively participate in Taijiquan. Conclusion: Teenagers have a low awareness of Taijiquan and lack a real and comprehensive understanding of taijiquan. The main way for teenagers to know Taijiquan is through watching taijiquan related films and TV works. At present, most popular taijiquan films and television works are exaggerated, which mislead teenagers' cognition of Taijiquan to some extent. Animation is a popular film and television works for teenagers. To vigorously develop high-quality taijiquan animation works is conducive to teenagers' understanding of Taijiquan, leading teenagers to practice Taijiquan and inheriting the new fashion of Taiji culture. Suggestions: (1) clear taijiquan transmission subject. The taijiquan film and television works should highlight the taijiquan subject status, as far as possible based on the objective and real Taijiquan, guide the youth group to have a comprehensive and objective cognition of taijiquan movement; (2) Grasp the traditional connotation of Tai Chi. Schools at all levels, Taijiquan clubs and taijiquan associations should increase the publicity of taijiquan traditional sports culture, create a good learning atmosphere of Taijiquan culture, and help young people better understand Taijiquan. (3) Innovate taijiquan promotion forms. The promotion of Taijiquan among young people should cater to their preferences and be good at using new media, visualization and animation technologies. A batch of high-quality Taijiquan animation works is urgently needed to guide young people to inherit Taijiquan.